A Little Bit of Dalba Goes a Long Way: Dalbavancin Use in a Vulnerable Patient Population. (4th October 2017) - Bryson-Cahn, Chloe; Beieler, Alison; Chan, Jeannie; Senter, Steve; Harrington, Robert; Dhanireddy, Shireesha
Abstract: Background: Serious staphylococcal infections require prolonged courses of intravenous (IV) antibiotics. Weekly IV dalbavancin is an alternative to more frequent IV antimicrobial dosing for homeless patients or persons who inject drugs (PWID), for whom creating a treatment plan can be challenging. We examined the clinical outcomes in patients who were treated with dalbavancin compared with a similar population treated with alternative antibiotics. Methods: We identified 18 patients who received dalbavancin from June 1, 2015 to December 31, 2016 using pharmacy records and 89 patients receiving IV antibiotics for similar infections treated at Harborview Medical Center from January 1, 2015 to May 31, 2015, before dalbavancin was available. Medical records were reviewed, and patient demographics, length of stay (LOS), readmission, and outcomes were abstracted using REDCap, linked to the University of Washington's Clinical Data Repository. Results: Basic demographics in Table 1. The types of infections are in Figure 1. Clinical cure rates were similar between the two groups (Figure 2) although 21% and 28% of the patients were lost to follow-up in the pre and post dalbavancin period. Among the subgroup of PWID, those who received dalbavancin had higher rates of clinical cure (64.7% vs. 29.4%, P = 0.01), a trend toward decreased LOS (11.4 ± 5.8 vs. 20.2 ± 15.1 days, P = 0.04), and fewer 30-day readmissions (0% vs. 29.4%, P = 0.02) (Figure 2). Fewer PWID in the dalbavancin group were lost to follow-up (23.5% vs. 70.6%). Conclusion: Patients treated with dalbavancin had similar outcomes compared with patients treated in the pre-dalbavancin time period. Among PWID, dalbavancin use led to significantly improved outcomes including a higher clinical cure rate, lower readmission rate, and shorter hospital LOS, which offset the cost of the drug. Dalbavancin is an option for the treatment of serious staphylococcal infections in selected patients. Disclosures: All authors: No reported disclosures.